Transforming Constructivist Learning into Action: Design Thinking in education - Scheer, Andrea; Noweski, Christine; Meinel, Christoph (Design and Technology Education: An International Journal, 2012)
In an ever changing society of the 21st century, there is a demand to equip students with meta competences going beyond cognitive knowledge. Education, therefore, needs a transition from transferring knowledge to developing individual potentials with the help of constructivist learning. Advantages of constructivist learning, and criteria for its realisation have been well-determined through theoretical findings in pedagogy (Reich 2008, de Corte, OECD 2010). However, the practical implementation leaves a lot to be desired (Gardner 2010, Wagner 2011). Knowledge acquisition is still fragmented into isolated subjects. Lesson layouts are not efficiently designed to help teachers execute a holistic and interdisciplinary learning. As is shown in this paper, teachers are having negative classroom experience with project work or interdisciplinary teaching, due to a constant feeling of uncertainty and chaos, as well as lack of a process to follow. We therefore conclude: there is a missing link between theoretical findings and demands by pedagogy science and its practical implementation. We claim that, Design Thinking as a team-based learning process offers teachers support towards practice-oriented and holistic modes of constructivist learning in projects. Our case study confirms an improvement of classroom experience for teacher and student alike when using Design Thinking. This leads to a positive attitude towards constructivist learning and an increase of its implementation in education. The ultimate goal of this paper is to prove that Design Thinking gets teachers empowered to facilitate constructivist learning in order to foster 21st century skills.